Jews: an Historical Exploration through the shores of Kerala History - Sumi Mary Thomas (IOSR Journal Of Humanities And Social Science, 2015)
Kerala, also known as Gods own Country, is a state in the South West region of India. The state was formed on November 1956 by combining various Malayalam speaking regions. From the early days Kerala is famous for trade, particularly for spices which attracted traders from different parts of the world. As per Sumerian records Kerala is referred as the ‘Garden of spices’ or ‘The spice garden of India’. The state has attracted Babylonians, Assyrians, Egyptians, Arabs, Greeks and Romans. Merchants from West Asia and Southern Europe established coastal ports and settlements in Kerala. Jewish connection with Kerala was started in the tenth Century B C. The Jews are an ethnic group who settled first in Muziris, the earliest seaport in Kerala which was known as ‘Little Jerusalem’. They came to Kerala during the period of King Solomon. It is believed that King Solomon had visited Kerala for trade purposes. From the very early days the country Kerala was known to the ancient Jews. In the 6 th century BC the Jews came to Kodungaloor in order to escape from the Babylonian captivity of Nebuchednezzar. In 580 B C the Babylonian Empire conquered Yehudah (Judah), the Southern region of ancient Israel. After 50 years later, the Persian Empire (ancient Iran) conquered the Babylonian Empire and allowed the Jews to return home to the land of Israel. But most of the Jews remained in Babylonia, some remained in today’s Iraq and Iran, and some migrated to neighboring lands of Central and East Asia including India, China, Afghanistan, Egypt, Yemen etc. When St.Thomas came to Kerala in 52 AD, there were a large number of Jews in Kerala. St.Thomas and his disciples tried to proselytize the Jews to Christianity. They came to Kerala in about 68 A D at Muziris or Kodungaloor and extended to Quilon, Madayi, Pantalayani Kollam, Chowghat, Chenamangalam, Madai, Paalayur, Mala, Pullut etc. The Jews lived a strong community life and they were protected by the native rulers. The Kulashekara Kings granted several privilages to the Jews. They were granted the famous Jewish copper Plate grant in 1000 AD by the Chera Emperor, Bhaskara Ravi Varman. The Jewish hill known as Joodakunnu and the Jewish tank Joodakulam at Madai depict close relation between the Jews and the Keralities